Integrating defense and leaf economic spectrum traits in a tropical savanna plant - Mohanbabu, Neha; Veldhuis, Michiel P.; Jung, Dana; Ritchie, Mark E. (Frontiers in Plant Science, 2023)
Allocation to plant defense traits likely depends on resource supply, herbivory, and other plant functional traits such as the leaf economic spectrum (LES) traits. Yet, attempts to integrate defense and resource acquisitive traits remain elusive. To address this, we assessed intraspecific covariation between different defense and LES traits in a widely distributed tropical savanna herb, Solanum incanum, a unique model species for studying allocations to physical, chemical, and structural defenses to mammalian herbivory. We found that in a multivariate trait space, the structural defenses - lignin and cellulose - were positively related to the resource conservative traits - low SLA and low leaf N. Phenolic content, a chemical defense, was positively associated with resource acquisitive traits - high SLA and high leaf N - while also being associated with an independent third component axis. Both principal components 1 and 3 were not associated with resource supply and herbivory intensity. In contrast, spine density - a physical defense - was orthogonal to the LES axis and positively associated with soil P and herbivory intensity. These results suggest a hypothesized “pyramid” of trade-offs in allocation to defense along the LES and herbivory intensity axes. Therefore, future attempts to integrate defense traits with the broader plant functional trait framework, such as the LES, needs a multifaceted approach that accounts for unique influences of resource acquisitive traits and herbivory risk.